Closing ceremonies and celebration of outcomes with Delwin Benson - Benson, Delwin E., director and speaker; Peterson, Kesley Arline, producer; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Remarks cover: What we accomplished here -- Visual overviews -- What we can accomplish next -- Next venue -- International home -- Use of LandHelp for conservation communications and home for congress proceedings -- Video production and uses.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses